Sirru Taqdiimi Kalimati At-Taqwa ala Al-Ilmi Fii Surah Al-Baqarah (Dirasah Dalaliyyah Siyaaqiyah) - Rochmad Rochmad; A. Fadly Rahman Akbar; Intan Pratiwi Mustikasari; Rizal Nur Haqoni (Buletin Al-Turas, 2025)
Purpose The aim of this study is to reveal two important aspects: first, to uncover the secrets of the words "taqwa" (piety) and "ilm" (knowledge) through the application of the principle of taqdim wa ta'khir (precedence and delay).   Method This study used a library research approach using primary and secondary sources. This study was conducted using a descriptive method, a scientific approach involving the collection and organization of data related to the aspects of taqwa (piety) and ilm (knowledge). The researcher also utilized an analytical method to examine the precedence of the word taqwa over ilm in the Qur'an through a contextual semantic analysis.   Results/findings The text discusses the significance of prioritizing taqwa (piety) over knowledge in several verses of Surah Al-Baqarah. In verse 194, taqwa is emphasized in retribution to avoid excessiveness. In verse 196, taqwa is highlighted as a part of obedience to Allah. In verse 203, the importance of taqwa in the rituals of Hajj is shown as a reminder of responsibility before Allah. In verse 223, taqwa prepares the soul for knowledge and its application. In verse 231, taqwa is linked to Allah’s all-encompassing knowledge to ensure rights and interests. In verse 233, the importance of taqwa is emphasized in children’s rights and the relationship between parents. In verse 282, taqwa is presented as the foundation for guidance and continuous learning from Allah for the benefit of His servants.   Conclusion The results of this study indicate that the precedence of taqwa over ilm emphasizes taqwa as the foundation for behavior control, inner worship, and practices that ensure obedience to Allah. Taqwa prepares the soul for beneficial knowledge, protects it from deviations, and strengthens responsibility and self-discipline. Through taqwa, guidance, justice, and the preservation of rights according to Allah’s Sharia are achieved.